The Factors Associated with Outpatient Re-Visits at RSJ Dr. Radjiman Wediodiningrat Lawang - Salsabilah, Nabilah; Shaluhiyah, Zahroh; Mustofa, Syamsulhuda Budi (JURNAL INFO KESEHATAN, 2023)
The number of people with disorders is gradually increasing from one year to the next. In Indonesia, the estimated number of people with mental illness is around 450,000 with a severe mental illness where 31.5% of people with mental illness are shackled by their families and 15% do not seek any medical treatment. Patients with mental disorders are in a state of mindset and emotions that are unstable, so the role of the family is needed to help people with self-care activities. According to Andersen, there are three factors that impact health service utilization. Factors that influence include predisposing factors, enabling factors, and need factors. The purpose of this study was to determine the factors that are associated with re-visiting outpatients at Dr. Radjiman Wediodiningrat Lawang Mental Hospital. The research method is quantitative research with a cross-sectional study approach. The research sample was the family who accompanied the patient to make an outpatient re-visit with a total of 400 respondents. The sampling technique used was accidental sampling. The data analysis used in this study was the Chi-Square test. The results indicated that there was a significant relationship between knowledge (p-value: 0.006), attitude (p-value: 0.000), income (p-value: 0.032), family support (p-value: 0.00), and information support (p-value: 0.003) with the re-visit of outpatients at Dr. Radjiman Wediodiningrat Lawang Mental Hospital. Predisposing factors and enabling factors are both associated with re-visiting outpatients at Dr. Radjiman Wediodiningrat Lawang Mental Hospital. Future researchers are hoped to study other aspects such as hospital health service system components and need factors that may be associated to recurrent visits of mental illness patients by utilizing a more comprehensive questionnaire to acquire better information.